2011
DOI: 10.1111/j.1447-0756.2011.01648.x
|View full text |Cite
|
Sign up to set email alerts
|

Female sexual dysfunction: Facts and factors among gynecology outpatients

Abstract: This is a pioneer study in Bangladesh to postulate female sexuality, revealing pain disorder as most prevalent; the women with dysfunction were dissatisfied with their sexual life. In order to determine the cause of female sexual dysfunction, the topic needs further exploration involving intervention at regular medical investigations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
6
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 29 publications
(95 reference statements)
1
6
0
4
Order By: Relevance
“…Por el contrario, Stulhofer y cols (27), observaron que en mujeres croatas, la moralidad religiosa se asoció con la presencia de inhibición del deseo. Tener una pareja con disfunción sexual se evaluó en 3 de los 15 artículos revisados, encontrándose una asociación positiva significativa, siendo mayor el riesgo en el estudio de Grewal y cols (31).…”
Section: Discussionunclassified
“…Por el contrario, Stulhofer y cols (27), observaron que en mujeres croatas, la moralidad religiosa se asoció con la presencia de inhibición del deseo. Tener una pareja con disfunción sexual se evaluó en 3 de los 15 artículos revisados, encontrándose una asociación positiva significativa, siendo mayor el riesgo en el estudio de Grewal y cols (31).…”
Section: Discussionunclassified
“…For example, female cancer survivors would experience significantly negative sexual dysfunction due to treatment (Krychman & Millheiser, 2013), and cancer-related female sexual dysfunction did not seem to be appropriately acknowledged and addressed in primary care treatment settings (Bober, Carter, & Falk, 2013). Another survey in a gynecological outpatient department found that 51.8% of the participants (n = 137) reported sexual problems with the highest complaints of pain during intercourse (71.8%), reduced desire (54.9%), and orgasmic problem (43.66%; Jahan, Billah, Furuya, & Watanabe, 2012). For males diagnosed with rectal cancer, sexual dysfunction was reported frequently following treatment mainly caused by surgical damage resulting from lateral lymph node dissection (Nishizawa et al, 2011).…”
mentioning
confidence: 92%
“…De acordo com a Associação Americana de Psiquiatria (1994), entende-se disfunção sexual como distúrbios no desejo e nas alterações psicofisiológicas que caracterizam a resposta sexual e causam angústia e dificuldades interpessoais 2 . Muitos estudos mostram que esse distúrbio é altamente prevalente na população feminina [3][4][5][6][7] . O estudo americano National Health and Social Life Survey demonstrou que 43% das mulheres avaliadas apresentavam algum tipo de disfunção sexual 3 .…”
unclassified
“…O estudo americano National Health and Social Life Survey demonstrou que 43% das mulheres avaliadas apresentavam algum tipo de disfunção sexual 3 . Recentemente, um trabalho desenvolvido em Bangladesh revelou que 51,8% das pacientes estudadas queixavam-se de um ou mais problemas sexuais 4 . No Brasil, o Estudo do Comportamento Sexual do Brasileiro (ECOS) detectou dificuldade sexual em 30% das mulheres, cujas principais queixas foram falta de desejo (34,6%) e dificuldades para obtenção de orgasmo (29,3%) 5 .…”
unclassified
See 1 more Smart Citation